2011
DOI: 10.1155/2011/579427
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of InN Thin Films Grown on Si (110) Substrate by Reactive Sputtering

Abstract: Indium nitride (InN) thin films were deposited onto Si (110) by reactive sputtering and pure In target at ambient temperature. The effects of the Ar–N2sputtering gas mixture on the structural properties of the films were investigated by using scanning electron microscope, energy-dispersive X-ray spectroscopy, atomic force microscopy, and X-ray diffraction techniques. The optical properties of InN layers were examined by micro-Raman and Fourier transform infrared (FTIR) reflectance spectroscopy at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Besides that, the increases of the PL intensity are attributed to the larger surface area as compared to unetched Si samples. [14]. By increasing the etching time, the Raman peak position slightly shifted to toward lower frequency.…”
Section: Resultsmentioning
confidence: 92%
“…Besides that, the increases of the PL intensity are attributed to the larger surface area as compared to unetched Si samples. [14]. By increasing the etching time, the Raman peak position slightly shifted to toward lower frequency.…”
Section: Resultsmentioning
confidence: 92%
“…The deposition of AlN on c-sapphire at low temperature can promote the growth of other planes than (002) due to a twinning mechanism resulting from reduced internal electrostatic field that favors the growth with (101) planes parallel to the surface. In addition, the size of crystallites was calculated from the full width at half maximum of the (002) diffraction peak by using the Scherrer's formula [36][37]. Fig ( 4) shows the size of crystallites increases with N2% on both substrates and exhibits a similar trend to the (002) texture coefficient calculated by equation (3.2).…”
Section: Structure and Microstructurementioning
confidence: 64%
“…4 InN have large electron transport properties with low e®ective mass and contains a surface accumulation layer that sorts InN as an important material used for manufacturing of high-frequency optoelectronic devices. 5 The low e®ective mass for electrons o®ers high mobility to the charge carriers and high saturation velocity. It observed that InN at room temperature o®ers high peak drift velocity.…”
Section: Introductionmentioning
confidence: 99%